Low-intensity ultrasound directly modulates neural activity of the cerebellar cortex - Ruo-Shui Xu; Xue-Mei Wu; Zhi-Qi Xiong (Brain Stimulation, 2023)
Background: Low-intensity ultrasound is a noninvasive neuromodulation technique with the potential to focally manipulate deep brain activity at millimeter-scale resolution. However, there have been controversies over the direct influence of ultrasound on neurons, due to an indirect auditory activation. Besides, the capacity of ultrasound to stimulate the cerebellum remains underestimated. Objective: To validate the direct neuromodulation effects of ultrasound on the cerebellar cortex from both cellular and behavioral levels. Methods: Two-photon calcium imaging were used to measure the neuronal responses of cerebellar granule cells (GrCs) and Purkinje cells (PCs) to ultrasound application in awake mice. And a mouse model of paroxysmal kinesigenic dyskinesia (PKD), in which direct activation of the cerebellar cortex leads to dyskinetic movements, was used to assess the ultrasound-induced behavioral responses. Results: Low-intensity ultrasound stimulus (0.1 W/cm2) evoked rapidly increased and sustained neural activity in GrCs and PCs at targeted region, while no significant changes in calcium signals were observed responding to off-target stimulus. The efficacy of ultrasonic neuromodulation relies on acoustic dose modified by ultrasonic duration and intensity. In addition, transcranial ultrasound reliably triggered dyskinesia attacks in proline-rich transmembrane protein 2 (Prrt2) mutant mice, suggesting that the intact cerebellar cortex were activated by ultrasound. Conclusion: Low-intensity ultrasound directly activates the cerebellar cortex in a dose-dependent manner, and thus serves as a promising tool for cerebellar manipulation.